NATURAL HISTORY OF CONGENITAL ISOLATED MILD AORTIC VALVE AND MILD PULMONARY VALVE STENOSIS: A SINGLE CENTER FOLLOW-UP STUDY - Serra Karaca; Pelin Karaca Özer; Kazım Öztarhan (İstanbul Tıp Fakültesi Dergisi)
Objective: Most of the available information on the natural history of aortic stenosis (AS) and pulmonary stenosis (PS) in children is based on studies carried out over the past 35-40 years using cardiac catheterization. This study aimed to reveal the natural history of congenital isolated mild valvular AS and PS in children using serial Doppler echocardiographic examinations. Materials and Methods: A total of 125 children, 50 with mild AS and 75 with mild PS, who underwent Doppler echocardiography were included in this study. The prognoses of mild AS and PS were compared according to age, gender, and valvular gradient at the time of initial diagnosis. Results: The mean age of patients was 26.1±37.6 months at diagnosis. The mean follow-up duration was 27.65±21.60 (1- 120) months. There was a significant decrease in the final gradient of the PS group compared to the baseline (23.58±6.97 vs. 19.88±11.21 mmHg, p=0.001). In the AS group, there was an increase in the final gradient, which was more pronounced in patients ≤1-year-old (22.42±6.12 vs. 27.74±14.12 mmHg, p=0.002). Four percent of patients in the PS group and 12% of patients in the AS group progressed to moderate to severe stenosis. All patients who progressed in the PS group were ≤1-year-old and male. Conclusion: The results showed that mild PS had a better prognosis than mild AS and that the risk of progression in AS was higher. Careful follow-up should be performed in mild PS cases ≤1-year-old, especially in boys, since progression may be detected, even if infrequently. Mild AS should also be followed closely, as the disease may show progressive characteristics in all age groups.